A meta-analysis on the relationship of exosomes and the prognosis of lung cancer. Issue 15 (16th April 2021) - Xiang, Hui; Li, Fan; Luo, Jingying; Long, Wenting; Hong, Liuyan; Hu, Yuzhui; Du, Hongying; Yuan, Yunxiao; Luo, Miao
Abstract: Background: A lot of research evidence shows that exosomes play an indelible role in the prognosis of lung cancer, but there are many disputes. Therefore, we conduct a meta-analysis to further demonstrate. Methods: A literature retrieval was performed through a search of PubMed, Embase, Web of Science, Cochrane, CKNI, Wanfang, and other databases to locate documents from the literature that satisfied the inclusion criteria. There were four outcome indicators: overall survival (OS), disease-free survival (DFS), disease-specific survival (DSS), and progression-free survival (PFS). Subgroup analysis was conducted according to sample size, country, detection method, analysis method, and pathological type. Stata 14.0 software was used to evaluate the prognostic value of exosomes in lung cancer. Results: A total of 2456 patients with lung cancer from 29 studies in 16 articles were included. The expression level of exosomes was closely associated with the OS and DFS of patients, although no statistical difference was observed between exosomes and DSS or PFS. Eighteen studies with 2, 110 patients were evaluated to examine the prognostic value of exosomes in lung cancer by exploring the association between exosomes and OS. The results showed that exosomes were strongly associated with worse OS, and the combined hazard ratio (HR) was 2.01 (95% confidence interval [CI]: 1.70–2.39, P = .000). Six studies investigated the association between exosomes and DFS, and showed a pooled HR of 2.48 (95% CI: 1.75–3.53, P = .000). Conclusion: Our analysis indicated that the expression level of exosomes was closely associated with the OS and DFS of patients with lung cancer, suggesting that exosomes are associated with poor prognosis of lung cancer. Exosomes may be a new biomarker for the prognosis of lung cancer, although a large number of prospective studies are still needed to support this.